COVID-19 preventive behaviors based on the health belief model among people in Khueang Nai District, Ubon Ratchathani Province - Chaikoolvatana, Cholada; Bunmachu, Dueanphen; Chaikoolvatana, Anun; Saising, Nawaporm (Disease Control Journal, 2025)
This survey research was conducted to examine covid-19 preventive behaviors and community management approaches in caring for COVID-19 patients. The sample was residents from Ko Ae Subdistrict, Khueang Nai District, Ubon Ratchathani Province. Data were collected from January 1 to September 30, 2022. Quantitative data were collected from 456 participants using a questionnaire measuring 25 items on COVID-19 perception and 12 items on preventive behaviors related to COVID-19. The reliability of the questionnaire was validated with 30 similar participants, yielding Cronbach’s alpha coefficients of 0.83 and 0.90, respectively. Data were analyzed using descriptive statistics and multiple regression analysis. For the qualitative study, purposive sampling was used to recruit 30 key informants, including public health personnel, community leaders, and community representatives. The focus group discussions were conducted using semi-structured interviews. Qualitative data were analyzed using content analysis. The result showed that the majority of the sample had good COVID-19 preventive behaviors (71.93%). History of COVID-19 infection and perceived benefits of preventive practices could predict preventive behaviors for COVID-19 by 14.84%, with a statistical significance level of 0.05. Regarding community management of COVID-19 patients, it was found that participatory processes were implemented in collaboration with related organizations. Disease prevention and control measures should emphasize the benefits of preventive behaviors and promote community participation, which would enhance the sustainability and efficiency of implementation.